تأثير زاوية ميل الألواح الكهروشمسية على عمل مضخة مياه تعمل بالطاقة الشمسية في الساحل السوري (Latakia University Journal -Engineering Sciences Series, 2014)
يهدف البحث إلى دراسة تأثير زاوية ميل الألواح الكهروشمسية على كمية الماء المتدفقة باليوم لمضخة مياه تعمل بالطاقة الشمسية، وتحديد الزاوية المثلى لميل هذه الألواح في الساحل السوري خلال أشهر الصيف الأربعة. بينت الدراسة أن تغيير زاوية ميل الألواح الكهروشمسية من (25˚) إلى (35.5˚)، لم يؤثر على منحني العلاقة بين شدة الإشعاع الشمسي وتدفق المضخة خلال اليوم. لكن التأثير الحاصل هو انخفاض كمية الطاقة الشمسية الساقطة على الألواح الكهروشمسية في اليوم، ما أدى إلى انخفاض الاستطاعة الهيدروليكية للمضخة، وبالتالي انخفاض كمية الماء المتدفقة في اليوم. كما بينت الدراسة أن كمية الماء المتدفقة متقاربة عند الزاويتين (25˚) و(22˚) لميل الألواح، مع أفضلية للزاوية (22˚)، وانخفضت كمية الماء من شهر لآخر خلال الأشهر (حزيران، تموز، آب) بنسب لم تتجاوز (2.5%)، أما في شهر أيلول انخفضت حوالي (7.5%). و بقيت عند الزاوية (35.5˚) كمية الماء ثابتة تقريباً خلال الأشهر(حزيران، تموز، آب)، أما في شهر أيلول انخفضت حوالي (6%). وبينت الدراسة بأن كمية الماء المتدفقة انخفضت بنسب كبيرة عند الزاوية (35.5˚) بالمقارنة مع الزاويتين (25˚) و(22˚)، فبلغت نسبة الانخفاض (7.5%,9%,12%,13%) في الأشهر (حزيران، تموز، آب، أيلول) على التوالي. This research aims to study the effect of the tilt angle of PV panels on the daily discharge a water pump powered by solar energy, and to determine the optimal tilt of these panels during summer months in the Syrian coast. The results demonstrated that the change of the tilt angle of PV panels from (25˚) to (35.5˚) has no effect on the curve of the solar radiation intensity and flow rate. However, the resulting impact was represented by low amount of solar energy falling onto PV panels, resulting in a reduction in hydraulic energy of the pump and consequently low flow rate per day. The study showed that the amount of water flow rate at the two angels (25˚ and 22˚) for the tilt of panels was close, with preference for the angle (22˚). Reduction of water amount from one month to another during the months (June, July, August) didn't exceed (2.5%), while it was (7.5%) in September. At angle (35.5˚), water amount was approximately constant during June, July and August, while it decreased by (6%) in September. Flowing water largely decreased at angle (35.5˚) in comparison with the two angles (25˚and 22˚), so the reduction was (13, 12, 9 and 7.5%), respectively in June, July, August and September.